2001
DOI: 10.1002/mds.1102
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in an Asian population: A study in Singapore

Abstract: In face-to-face interviews, we examined 157 consecutive individuals aged 55 years and older, selected from the general population in Singapore, and 1,000 consecutive individuals aged 21 years and older, from a primary healthcare center. Based on the IRLSSG criteria, the prevalence of restless leg syndrome (RLS) was 0.6% and 0.1%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
4
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(147 citation statements)
references
References 12 publications
10
127
4
6
Order By: Relevance
“…The reported prevalence of RLS in European countries ranges between 5% and 15%, whereas it is considerably low, 0.1-2.3%, in Asian countries (20). The prevalence of RLS was found to be 3.4% in the western Black Sea coast of Turkey (21).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of RLS in European countries ranges between 5% and 15%, whereas it is considerably low, 0.1-2.3%, in Asian countries (20). The prevalence of RLS was found to be 3.4% in the western Black Sea coast of Turkey (21).…”
Section: Discussionmentioning
confidence: 99%
“…2-4 A prevalence of 5% to 15% has been reported in United States and Europe 5-7 with lower prevalence rates (< 5%) in Asian populations. 8 Epidemiologic studies have suggested an association between RLS and cardiovascular diseases, Parkinson disease, erectile dysfunction, poor sleep, and depressive symptoms. 9-11 The burden of RLS on quality of life 12 is comparable to that of other chronic illnesses such as diabetes, arthritis, hypertension, and acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…3 A prevalence of 0.1% has been observed in Singapore, 34 3.19% in Turkey, 35 6.77% in Mozambique (Africa), 36 and 6.4% in Brazil. 37 The different prevalence rates observed in epidemiological studies were probably due to many factors such as ethnic composition of the population, environmental influence, and also the methodology used to obtain the data.…”
Section: Restless Legs Syndromementioning
confidence: 99%